1 - Linguistic Diversity, Pluralism and National Development in Africa: https://doi.org/10.4314/ad.v34i2.57364 - Chumbow, Beban Sammy (Africa Development, 2009)
In the quest for national development in Africa, how are the facts of linguistic diversity to be reconciled with pluralism, the African Union’s ideological option for nation building? From the perspective of language planning theory, we motivate, justify, rationalise and propose a tier stratification model of language planning predicated on an adaptation of Jurgen Habermas’s 1965 notion of the public sphere. Concretely, the bifurcation of the public sphere into the public and private domains and a principled stratification of languages of the nation-state into these domains, leads to a rational planning process. The process is characterised by the maintenance and consolidation of the linguistic and cultural identities of ethno linguistic communities at the micro- planning level while constructing a pluralistic national identity at the macro-planning level. The efficacy of the interaction between the two domains is mediated by two principles. The Principle of Functional Complementarities (PFC) requires that all languages be assigned (by the state) some valorising functions, i.e. functions that procure economic, social, and political advantages, thereby contributing to elevating the status of the ethno-linguistic communities. The Principle of Attitude Engineering (PAE) is expected to effect a positive change of attitude, culminating in a change of mindset congruent with the paradigm shift of national development anchored on pluralism. This model of Language Planning ensures the empowerment of linguistic minorities, provides for a reduction of ethno linguistic dominance and ipso facto, ensures the democratisation of access to knowledge, especially development-relevant knowledge for the national development enterprise.